DENGAN PENDEKATAN MATRIKS DALAM REGRESI - Chandra Utama (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
Regression is a model that is usually used in many field of study, include economics and business, in a purpose to find causal relation of independent variable to dependent variable. It is described the relation of one or more independent variables to one dependent variable. In many cases, the regression with more than two independent variables is estimated by wrong formula or equation. The fallacy usually exist because statistical or econometrics tax book, which is used as reference, often show only the regression formula for maximum two independent variables. On the other side, it is not much explanation how the formula can be employed to find the coefficient of regression. There are many cases that researchers used formula to calculate coefficient for two independent variables in calculation of more than two independent variables. This paper uses matrix analysis to find formula of regression as well as calculate it by using matrix approach because the development of formula of coefficient in regression can be explained clearly by matrix approach. The different formula and equation must be used in different number of independent variable is concluded by this paper. All variables that used in the model are always calculated in every formula of coefficient.